(untitled) (Research, Society and Development, 2020)
The study aimed to assess the prevalence of metabolic syndrome and its association with the nutritional status of the elderly assisted by the Family Health Strategy in the city of Teresina, Piauí. This is a cross-sectional study, carried out with 273 elderly people. Information on the characteristics of the participants was obtained through the application of a structured questionnaire. The anthropometric evaluation considered data related to weight, height, waist circumference and the waist-to-height ratio. Laboratory tests (glucose and lipid profile) and blood pressure were analyzed. For the diagnosis of metabolic syndrome, it used the NCEP/ATP III criteria. The results showed that part of the elderly have metabolic syndrome and that there was an association with anthropometric, biochemical and hemodynamic variables. Thus, it is recommended to implement monitoring and control policies and strategies to reduce the prevalence of this complex disease, thus improving the care provided and the quality of life of the elderly, with a focus on lifestyle changes, adoption of healthier eating habits and physical activity.